Pentacyclic triterpenoids saponins pannosides A-E from Tripolium pannonicum - Um, Soohyun; Lee, Jaeyoun; Lee, Yechan; Namkung, Wan; Kim, Seung Hyun (Frontiers in Marine Science, 2023)
Five previously undescribed pentacyclic triterpenoid saponins, pannoside A–E (1–5), were discovered from the whole plant of seashore aster, Tripolium pannonicum, collected from the Songdo tidal flat, Incheon, Korea. The planar structures of pannosides were elucidated as pentacyclic triterpenoids bearing sugar moieties and 3-hydroxybutyrate (3-HB) based on the interpretation of the NMR, IR spectroscopic and MS data. The relative configurations of the aglycone and sugar moieties of 1–5 were determined based on careful analysis of ROESY correlations. To determine the absolute configuration of 3-hydroxybutyrate, we utilized the phenylglycine methyl ester (PGME) derivatization with LC-MS chromatographic analysis. Pannoside E (5) exhibited inhibitory activities against diverse cancer cell lines including prostate carcinoma and non-small cell lung carcinoma, with IC50 values of 0.34 and 0.89 μM, respectively. Pannosides are the first triterpenoid saponin isolated from T. pannonicum, implying that undiscovered secondary metabolites from a halophyte could be a good source of bioactive compounds.